The experience of sessional teachers in nursing: A qualitative study. (November 2015) - Dixon, Kathleen A.; Cotton, Antoinette; Moroney, Robyn; Salamonson, Yenna
Summary: Background: Worldwide, there is a growing reliance on sessional teachers in universities. This trend is reflected in an undergraduate nursing program in a large Australian metropolitan university where a significant proportion of contact hours is staffed by sessional teachers, yet little is known about what type of support is needed for sessional teachers to optimise their capacity to contribute to the academic program. Objectives: To describe the experiences of sessional teachers in a Bachelor of Nursing program in an Australian university. Design: This is an exploratory qualitative study; fifteen sessional teachers were interviewed using semi-structured questions to explore their experiences of teaching. Setting: This study was conducted in a large metropolitan school of nursing located on three sites. Participants: A purposive sample of 15 sessional teachers was interviewed for this study. Methods: Semi-structured interviews were conducted face to face. Thematic analysis was used to identify major themes in the interview data and collaborative analysis was undertaken to ensure rigour. Results: Findings revealed that sessional teachers enjoyed teaching, were committed to their role and viewed their clinical currency as a valuable asset for teaching. However, participants also spoke about wanting a sense of belonging to the School, with most feeling they were "outsiders". Areas identified for improvement included system and process issues, micro teaching and assessment skills, classroom management and timely access to resources. Conclusion: There is a need to improve sessional teachers' sense of belonging and to provide an inclusive structure and culture to optimise their capacity to contribute to the academic program.